PERANAN MARIA WALANDA MARAMIS DALAM MEMAJUKAN PENDIDIKAN KAUM PEREMPUAN DI KABUPATEN MINAHASA PROVINSI SULAWESI UTARA, TAHUN 1917-1924 - Irkfa Zuhayriah Tanjung; Kamaruddin Kamaruddin; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Education for the Indonesian nation is one of the most important sectors in national development and is made as the mainstay that functions as much as possible in an effort to improve the quality of human life. Indonesia is a large country with a long history, and many have historical figures, both historical figures on the island of Sumatra, Java, Kalimantan, Sulawesi, and other islands. As one example in the Minahasa region of North Sulawesi province was born a female education leader who struggled to raise the dignity of women in his day. The figure is Maria Walanda Maramis, is one of the figures that play a role in advancing education in Minahasa District, North Sulawesi Province, especially education for women. The objectives of this research are: (1) Knowing the life history of Maria Walanda Maramis (2) Knowing the background of the organization of Mother-to-Child Association (PIKAT) in Minahasa (3) Knowing the role of Maria Walanda Maramis in advancing education for women in Minahasa (4 ) Knowing the comparative role of Mary Walanda Maramis with her contemporaries (5) Knowing the end of Maria Walanda Maramis's struggle in advancing the education of women in Minahasa. The method used in this study is a historical method with an approach that explains the problem in a narrative and descriptive. The data obtained from the literature and documents available are then analyzed in their own language. Data analysis techniques used are using comparative study by making a comparison of the role of a character written with a character that his contemporaries. The result of this research is Maria Walanda Maramis is a prominent figure of woman education advocate to advance woman's education level in Minahasa, starting from establishing an organization that is Association of Mother to Child (PIKAT) aiming to make Minahasa woman become skilled and intelligent woman, so that Minahasa women after adulthood are not just waiting for prospective husbands to come apply but can earn income and when become a housewife to be a smart mother, on the other hand Maria Walanda Maramis also founded a school for women, can be seen from the efforts made Maria Walanda Maramis , has brought great changes to the people of Minahasa even Indonesia.Keywords: Maria Walanda Maramis, Role, Minahasa.JOM